RUSSIA'S ECONOMIC SECURITY: THREATS TO NATIONAL INTERESTS AND THEIR REFLECTION - M. N. Dudin; N. V. Ljasnikov; V. N. Sidorenko (Модернизация, инновация, развитие, 2015)
The relevance of this study due to the fact that at the present time the situation inRussiais complemented by the negative consequences of market reforms in the economy. According to statistical studies in the country with infl ation of about 10% per year among the total population of more than 20% of people with incomes below the subsistence minimum, and the income gap between the highest-income populations and low-income groups more than 12 times. The inequitable distribution of material and spiritual wealth, unemployment (over 9%), ignoring the legitimate rights and interests of a particular person and their direct violation, corruption, alcoholism, drug addiction largely led to the reproduction of aggression, violence in the country. The recession has limited the ability of the material support of the institutions of culture, education, health. The majority of the population is a feeling of uncertainty, future uncertainty, anxiety, loss of landmarks.Objectives The purpose of this work is the identifi cation and characterization of threats to economic security of theRussian Federationat the present time, and to develop recommendations for the prevention of threats to the national interests ofRussia.Method’s. The methodological basis of this article was legal, comparative and economic-statistical methods of analysis. Results. In the framework of the submitted article, the authors found that threats to the economic security ofRussiaare potential dangers that can occur when inept and ineffi cient use of economic resources ofRussiaon the domestic and foreign markets. Major threats to the economic security of theRussian Federationare: bankruptcy, weak absorption lines; corruption; threats to small business development; investment crisis, the massive outfl ow of capital; the crisis in the social sphere; food addiction; the crisis of industrial policy, as well as strengthening the role and place of TNCs.Conclusions and Relevance. The practical value of this work lies in the allocation of threats to the national interests ofRussiain the economic sphere, as well as the development of recommendations for their prevention.